Predictors of 30-day readmission following hospitalisation with community-acquired pneumonia. Issue 1 (26th March 2021) - Chakrabarti, Biswajit; Lane, Steven; Jenks, Tom; Higgins, Joanne; Kanwar, Elizabeth; Allen, Martin; Wotton, Dan
Abstract : Background: There is a paucity of UK data to aid healthcare professionals in predicting which patients hospitalised with community-acquired pneumonia (CAP) are at greatest risk of 30-day readmission and to determine which readmissions may occur soonest. Methods: An analysis of CAP cases admitted to nine UK hospitals participating in the Advancing Quality Pneumonia Programme. Results: An analysis was performed of 12 157 subjects hospitalised with CAP in the Advancing Quality Programme Database. 26% of those discharged were readmitted within 30 days with readmission predicted by comorbidity including non-metastatic cancer, diabetes with complications and chronic kidney disease. 41% and 66% of readmissions occurred within 7 and 14 days of discharge, respectively. Patients readmitted within 14 days were more likely to have metastatic cancer (6.6% vs 4.5%; p=0.03) compared with those readmitted at 15–30 days. Conclusions: A quarter of patients hospitalised for CAP are readmitted within 30 days; of those, two-thirds are readmitted within 2 weeks. Further research is required to determine whether such readmissions might be preventable through imple menting measures including in-hospital cross-specialty comorbidity management, convalescence in intermediate care, targeted rehabilitation and advanced care planning.